(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This abstract explores the intricate gender dynamics portrayed in contemporary Indian English literature, emphasizing the evolution of themes and narratives through feminist perspectives. Indian literature in English has undergone a significant transformation with the advent of feminist ideologies, reflecting a diverse range of experiences and challenges faced by women in Indian society. Authors such as Arundhati Roy, Anita Desai, and Kiran Desai have contributed seminal works that critique patriarchal norms, explore women's agency, and depict the intersectionality of gender with class, caste, and other social identities.The abstract delves into how these narratives not only challenge traditional gender roles but also amplify marginalized voices and redefine notions of femininity and masculinity. Themes of identity, sexuality, and empowerment are recurrent in these literary works, offering nuanced insights into the complexities of gender relations in contemporary India. By examining the contributions of feminist discourse to Indian English literature, this abstract highlights literature's role in reflecting societal changes and advocating for gender equity. Ultimately, this study aims to underscore the ongoing relevance of gender dynamics in shaping literary discourse and fostering a deeper understanding of social justice issues within the Indian cultural context.